Smoking cessation by nicotine transdermal patch and gum: A Review - Hussain, Hamid; Siddiqui, Muhammad Asad; Jamal, Qaiser; Aziz, Muhammad Owais; Javaid, Arshad (Annals of Allied Health Sciences, 2017)
Background World Health Organization recognizes smoking as a major public health issue all over the world. Nicotine replacement therapy (NRT) is to be considered as one of the best smoking cessation strategies so far. Most widely used NRT are nicotine gum and nicotine patches. The aim of this review is to determine the most effective and appropriate nicotine therapy for smoking cessation after making comparison between two most commonly used NRT, nicotine gum and nicotine transdermal patch. Method We systemically searched electronic databases including Medline, Scopus, PubMed, CINAHL, and Cochrane to review published literature in this area. Electronic searches were limited to smoking cessation, nicotine replacement therapy, nicotine gum, nicotine transdermal patch, and effectiveness. All placebo randomized controlled trials which investigated the effectiveness of NRT were eligible for this systematic review. Both male and female healthy participants who smoked more than 20-cigareetes per day were eligible for this systematic review with 20 to 65 years’ age limit. Results A total of 975 articles were searched from above mentioned databases using the keywords. The number was dropped to 156 upon exclusion of repeated and irrelevant studies. Out of these 156 articles, 129 were excluded as titles or abstracts did not match eligibility criteria leaving 27 for this review. However, only 15 articles were included in this review following further screening, study population, intervention, or outcome of studies that did not met the selection criteria were excluded. Conclusion It was concluded that nicotine transdermal patch is more effective and more helpful as compared to nicotine gum in smoking cessation. In the light of result, it has also been recommended that nicotine transdermal patch must be used as a first priority in smoking cessation to achieve the target rather than nicotine gum